Effectiveness of STEM Approach for Understanding Membrane Formation in Biology - Gupta, Manisha Bajpai; Bajpai, Medha (International Journal of Membrane Science and Technology, 2023)
Research paper aims to explore the relevance and effectiveness of STEM approach through virtual learning for membrane formation in biology in the Indian context. In present scenario, it observed conventional approaches have very limitation for biology learning. Presently STEM approach give opportunity through virtual learning to promote collaborating and inquiry based learning. STEM is emerging as one of the most effective approach for learning. The present study was conducted to explore the effectiveness of STEM approach for understanding membrane formation in Biology. The main purpose of this study was to investigate the effectiveness of STEM approach for understanding of concepts of biology. The findings of the present study clearly revealed that student understand the concept of membrane formation through STEM approach in a better way as compared to conventional approach. This paper is a humble attempt to discuss position of STEM approach, initiatives of Government of India, and the impact it has on student learning and overall educational outcomes in India.